Clinical features and outcomes of bacterascites in cirrhotic patients: A retrospective, multicentre study. (17th March 2020) - Li, Beiling; Gao, Yanhang; Wang, Xianbo; Qian, Zhiping; Meng, Zhongji; Huang, Yan; Deng, Guohong; Lu, Xiaobo; Liu, Feng; Zheng, Xin; Li, Hai; Chen, Jinjun
Abstract: Background & Aims: Current guidelines on the management of bacterascites are limited. This multicentre, retrospective study investigated the clinical features and outcomes of cirrhosis patients with bacterascites. Methods: Two series of cirrhosis patients were evaluated. The first included 418 patients with ascites‐positive cultures at 11 hospitals during 2012‐2018. Clinical characteristics and outcomes were recorded. The second included 208 patients with sterile ascites from a prospective cohort (NCT02457637). Clinical features and outcomes of cirrhotic patients with or without bacterascites were investigated. Results: In the first series, bacterascites was diagnosed in 254/418 (60.8%) patients, and culture‐positive spontaneous bacterial peritonitis (SBP) in 164/418 (39.2%) patients. Gram‐positive bacteria were more prevalent in bacterascites patients than in culture‐positive SBP patients (59.1% vs 22.0%; P < .001). For patients with acute‐on‐chronic liver failure (ACLF) in bacterascites and culture‐positive SBP groups, the 28‐day transplant‐free mortality (41.3% vs 65.5%; P = .015) and the prevalence of in‐hospital acute kidney injury (AKI) (84.8% vs 75%; P = .224). For patients without ACLF in the bacterascites (n = 208) and culture‐positive SBP groups (n = 108), the 28‐day transplant‐free mortalities were 13% vs 13.9% ( P = .822), the probabilities of progression to ACLF within 28 days were 10.1% vs 14.8% ( P = .216) and the prevalences of in‐hospital AKI were 14.4% vs 30.6% ( P = .001). Bacterascites patients had higher 28‐day mortality than those patients with sterile ascites, after propensity score matching (18.4% vs 8.6%; P = .010). Conclusion: Bacterascites patients had non‐negligible poor clinical outcomes, including in‐hospital AKI, progression to ACLF and 28‐day mortality. Future studies are warranted to expedite the diagnosis of bacterascites and optimize antibiotic treatment.